Imprisonment and Terrorism - Bove, Vincenzo (Terrorism and political violence, 2022)
While policymakers frequently praise the impact of law enforcement for addressing the threat of terrorism, several cases suggest that the imprisonment of terrorists and potential perpetrators may actually lead to (more) radicalization and, ultimately, a higher risk of terrorism. We take systematic stock of the arguments linking terrorism with incarceration and analyze newly collected data on worldwide prison populations. The results from quantitative analysis highlight that an increase in prison population is correlated with a decline in the number of terrorist attacks, in particular its domestic form. We conclude with a discussion of the implications of this finding for academic and policy circles.